The lateral habenula contributes to regulation of body temperature - Xuxin Wang; Xiaowei Chen; Zehui Zhang; Xiaofeng Liu; Qianqian Lv; Meiying Song; Danyang Zhao; Jianjun Su; Yana Su; Guoyan Zhao; Jianfeng Sun; Weihong Lin; et al. (iScience, 2025)
Summary: The lateral habenula (LHb) is implicated in the regulation of numerous physiological functions, particularly those associated with thermoregulation. It exhibits close anatomical and functional connections with the key brain regions that play a crucial role in regulating body temperature. However, whether the LHb directly contributes to temperature regulation remains unclear. We here report that chemogenetic and optogenetic manipulations of LHb glutamatergic neurons bidirectionally modulated body temperature. When the LHb glutamatergic neurons were impaired, mice exhibited a pronounced intolerance to cold stimuli. Interestingly, we observed differential responses to thermal stimuli between GABAergic neurons in LPO and glutamatergic neurons in LHb. Notably, cold-activated glutamatergic neurons in LHb receive the projections from heat-activated GABAergic neurons in LPO. Using optogenetic techniques to activate the LPOVgat–LHb neural circuit led to significant decreases in body temperature. Collectively, our findings suggest that the glutamatergic neurons in the LHb and the LPOVgat–LHb neural circuit may play a crucial role in temperature regulation.